Thiol-norbornene gelatin hydrogels: influence of thiolated crosslinker on network properties and high definition 3D printing. (31st December 2020) - Van Hoorick, Jasper; Dobos, Agnes; Markovic, Marica; Gheysens, Tom; Van Damme, Lana; Gruber, Peter; Tytgat, Liesbeth; Van Erps, Jürgen; Thienpont, Hugo; Dubruel, Peter; Ovsianikov, Aleksandr; Van Vlierberghe, Sandra
Abstract: Photocrosslinkable gelatin hydrogels are excellent bioinks or biomaterial ink components to serve biofabrication applications. Especially the widely investigated gelatin-methacroyl (gel-MA) hydrogels hold an impressive track record. However, over the past decade, increasing attention is being paid to thiol-ene photo-click chemistry to obtain hydrogel networks benefitting from a faster reactivity (i.e. seconds vs minutes) along with superior biocompatibility and processability. In order to exploit this photo-click chemistry, often an ene-functionality (e.g. norbornene) is introduced onto gelatin followed by crosslinking in the presence of a multifunctional thiol (e.g. dithiothreitol). To date, very limited research has been performed on the influence of the applied thiolated crosslinker on the final hydrogel properties. Therefore, the present work assesses the influence of different thiolated crosslinkers on the crosslinking kinetics, mechanical properties and biological performance of the hydrogels upon encapsulation of primary adipose tissue-derived stem cells which indicated a cell viability exceeding 70%. Furthermore, the different formulations were processed using two-photon polymerization which indicated, in addition to differences in processing window and swelling ratio, a previously unreported phenomenon. At high intensities (i.e. ⩾150 mW), the laser results in cleavage of the gelatin backbone even in the absence of distinct photo-cleavable functionalities. This can have potential to introduce channels or softer regions in gels to result in zones characterized by different degradation speeds or the formation of blood vessels. Consequently, the present study can be used to provide guidance towards tailoring the thiol-ene system towards the desired applications.